Left. No. 76, What they say about the Beveridge Report ([London : Controversy Pub. Co.])
1943-01 1943 1940s 8 pages JANUARY, 1943 : No. 76 LEFT FOURPENCE VANSITTARTISM IN THE LABOUR MOVEMENT THE ENEMY WITHIN THE GATES BEVERIDGE (1) What They Say About the Report: a Documentary of Opinion (2) Soviet Social Insurance and the Beveridge Report: a Comparison By E. STRAUSS The MEANING of FASCISM C. A. SMITH CHALLENGES THE ACCEPTED VIEW 172/BE/7